2022
DOI: 10.3389/fonc.2022.832763
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant May Falsely Increase 17β-Estradiol Levels in Immunoassays: A Case Report of a 57-Year-Old Postmenopausal Patient With Recurrent Estrogen Receptor-Positive Breast Cancer

Abstract: The prognosis for female patients with locoregionally recurrent breast cancer has improved with the concurrent local and systemic treatment under multiple disciplinary teams. Radiotherapy is a valuable local treatment measure for unresectable locoregional recurrent breast cancer; however, reirradiation in previously irradiated areas is still a matter of debate. Antihormonal therapy achieves an overall survival benefit for most of these patients with estrogen receptor-positive (ER+) breast cancer in both adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Additionally, a postmenopausal breast cancer patient treated with fulvestrant, an estrogen receptor antagonist, had gradually increasing estradiol concentrations measured by immunoassay. When the same samples were measured by LC-MS/MS, the estradiol concentrations were in the postmenopausal reference interval, as expected [ 32 ]. As can be appreciated, the added specificity available through use of LC-MS/MS mitigates the issues that immunoassays may have with cross-reactivity.…”
Section: Estradiolsupporting
confidence: 78%
“…Additionally, a postmenopausal breast cancer patient treated with fulvestrant, an estrogen receptor antagonist, had gradually increasing estradiol concentrations measured by immunoassay. When the same samples were measured by LC-MS/MS, the estradiol concentrations were in the postmenopausal reference interval, as expected [ 32 ]. As can be appreciated, the added specificity available through use of LC-MS/MS mitigates the issues that immunoassays may have with cross-reactivity.…”
Section: Estradiolsupporting
confidence: 78%
“…The chemical structure similarity between estradiol and fulvestrant makes it impossible for the antibodies used in the immunoassays to distinguish among them ( 15 , 16 ). Consequently, an increase in estradiol level due to cross-reaction with fulvestrant is observed ( 12 , 14 ). In our study, we confirmed the interference of fulvestrant in the estradiol measurement by Centaur CP immunoassay and proposed a simple laboratory tool that allows to differentiate false cases from actual ovarian escape.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) leading to a cross-reactivity in estradiol immunoassays ( 11 ). A few case reports ( 12 , 13 , 14 ) have been published concerning fulvestrant measured as estradiol by the commercial immunoassays and inducing falsely elevated estradiol results. This is a problem for clinicians and laboratory staff and may wrongly impact medical decisions.…”
Section: Introductionmentioning
confidence: 99%